Dynamics of thin walled composite beams: Analysis of parametric uncertainties - Piovan, Marcelo Tulio (2013)
This article is concerned with the stochastic dynamic analysis of structures constructed with composite materials. Depending on many aspects (manufacturing process, material uncertainty, boundary conditions, etc.) real composite structures may have deviations with respect to the calculated response (or deterministic response). These aspects lead to a source of uncertainty in the structural response associated with constituent proportions, geometric parameters or other unexpected agents. Uncertainties should be considered in a structural system in order to improve the predictability of a given modeling scheme. In this study a model of shear deformable composite beams is employed as the mean model. The probabilistic model is constructed by adopting random variables for the uncertain parameters of the model. This strategy is called parametric probabilistic approach. The probability density functions of the random variables are constructed appealing to the Maximum Entropy Principle. The continuous model is discretised by finite elements and the Monte Carlo method is employed to perform the simulations, thereafter a statistical analysis is performed. Numerical studies are carried out to show the main advantages of the modeling strategies employed, as well as to quantify the propagation of the uncertainty in the dynamics of slender composite structures.